Whistle - blowing as a panacea for corruption in Nigeria: an impetus of whistleblowers' protection policies satisfaction / Muritala Dauda, Mohammad Zaki Ahmad and Mohammad Faisol Keling - Dauda, Muritala; Ahmad, Mohammad Zaki; Keling, Mohammad Faisol (Research Management Centre (RMC), 2020)
The scourge of corruption which has almost eaten up the entire Nigeria's economy is not in any way a new phenomenon in the country. Series of attempt have been made by Nigeria's past administrations to stop the cankerworm from its manifestation which yielded little or no success. However, the giant stride made by present administration through the introduction of whistle-blowing as a mechanism to fight corruption and other misconduct in Nigeria has been a welcome development in the country. This has given Nigerians the opportunity to expose wrong doing and all sorts of unethical activities in the society as part of contributing their quotas to the development of the country. The study emphasized on the significant contribution and the role played by whistle-blowers towards the recovery of looted funds in Nigeria. Similarly, the study has discovered that the government can do more by making adequate legal protection for the whistle-blowers in order to encourage them towards their participation in the fight against corruption and nefarious activities in the country. If otherwise, the Nigerian government may not achieve its objective. The study equally sensitizes Nigerian policy makers and the citizens on the likely dangers if the whistle-blower's protection law is not passed and ratified by the highest law-making body of Nigeria (The National Assembly). The paper therefore, employs exploratory research method through the use of secondary data to examine the influence of whistle-blowing on corruption and other misconduct in Nigeria.